Comparison of Corneal Densitometry and Visual Acuity Refractive Results after Alcohol-Assisted and Mechanical (Rotating Brush) Epithelium Removal Techniques in Myopic Photorefractive Keratectomy - Igor Knezović; Sara Djurić; Nada Vrkić; Andjelko Parać; Nina Jovanović (Acta Clinica Croatica, 2024)
The aim was to compare corneal densitometry, haze development, visual and refractive results after photorefractive keratectomy (PRK) performed with different epithelial removal techniques. This study included 42 patients (84 eyes) who underwent PRK with one eye de-epithelialized with 20% ethanol solution (PRK-a group) and another one with rotating brush (PRK-b group). The procedures were performed by the same surgeon on the same laser platform after comprehensive preoperative assessment. Follow up examinations of the patients were scheduled on postoperative day 4, then 1, 3 and 12 months postoperatively. Faster recovery of visual acuity was achieved in the PRK-b group during 12-month postoperative period but differences were statistically nonsignificant. Haze was significantly less present in the brush group measured 12 months after surgery. Also, eyes in the PRK-b group returned close to its basal corneal densitometry values faster than those that underwent PRK-a. Short-term visual recovery occurred faster in the PRK-b group. Less haze development and better corneal transparency were achieved in the PRK-b group throughout the 12-month follow-up period. However, both procedures showed great results and patient satisfaction was high regardless of the de-epithelialization method.